PENEGAKAN HUKUM TERHADAP PERDAGANGAN PRODUK BARANG ILEGAL BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Winda Yunita; Riza Yudha Patria (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2022)
Article 62 of the Criminal Code states that trading in illegal goods is a crime, and this is enforced in conjunction with other laws that protect consumers. How is law enforcement against trade in illegal goods products based on Law Number 8 of 1999 concerning Consumer Protection. What are the disincentives for law enforcement efforts against the crime of counterfeiting illegal products? This study uses a legal-regulatory approach. Based on the results of the study and discussion, it shows that law enforcement in relation to trade in illegal commercial products based on Law Number 8 of 1999 "Consumer Protection" is carried out through the application of criminal law (criminal law enforcement) and peer review by the National Police and the Food and Drug Supervisory Agency ( BPOM). The perpetrators of trafficking in illegal goods are handled legally at the judicial level based on legal provisions and one of its enforcement is carried out by a decision with a permanent res judicata (inkracht van gewijsde) in order to obtain criminal sanctions and guarantees of legal certainty. others: The criminal sanctions of Article 62(1) in conjunction with Article 8 and Article 9(2) of the Consumer Protection Law Number 8 of 1999 do not have a deterrent effect. Keywords: Trade, Illegal Goods Products, Consumer Protection.